Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11154-007-9029-1
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine physiology of kisspeptin in the human

Abstract: Kisspeptin is a 54-amino acid peptide, encoded by the KiSS-1 gene, which activates the G protein-coupled receptor GPR54. Recent evidence suggests the kisspeptin/GPR54 system is a key regulator of reproduction. GPR54-deficient mice have abnormal sexual development. Central or peripheral administration of kisspeptin stimulates the hypothalamic-pituitary-gonadal (HPG) axis in animal models. This review discusses the evidence that kisspeptin also plays a key role in human reproduction. Inactivating GPR54 mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 38 publications
0
13
0
3
Order By: Relevance
“…Kisspeptins which bind to the G-protein-coupled receptor (GPR54) are a family of neuropeptides and are coded by the KiSS-1 gene. 1,2 The KiSS-1 gene encodes a 145-amino-acid protein that is enzymatically cleaved into a 54-amino-acid peptide, known metastin, as well as shortened peptides of 14, 13, or 10 amino acids (kisspeptin-54, kisspeptin-14, kisspeptin-13 and kisspeptin-10, respectively). 2 In 2001, several groups reported that all of the kisspeptins bind the same receptor (known as GPR54).…”
Section: Introductionmentioning
confidence: 99%
“…Kisspeptins which bind to the G-protein-coupled receptor (GPR54) are a family of neuropeptides and are coded by the KiSS-1 gene. 1,2 The KiSS-1 gene encodes a 145-amino-acid protein that is enzymatically cleaved into a 54-amino-acid peptide, known metastin, as well as shortened peptides of 14, 13, or 10 amino acids (kisspeptin-54, kisspeptin-14, kisspeptin-13 and kisspeptin-10, respectively). 2 In 2001, several groups reported that all of the kisspeptins bind the same receptor (known as GPR54).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, I discuss key aspects of sexual differentiation of the brain and behavior as it relates to the recently-identified neuronal Kiss1 system. Several other papers have extensively reviewed the current literature on the Kiss1 system (including kisspeptins and their receptor GPR54), particularly in relation to reproduction and puberty (50, 78, 80, 84) as well as human clinical issues (2, 11, 22, 44, 85). In the present paper, I provide some essential background on Kiss1 biology and then focus on the latest findings connecting the kisspeptins and GPR54 to sexual differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A vast array of data has linked KISS1‐KISS1R signalling to the onset of puberty in many species (for reviews, see Kuohung & Kaiser 2006; Smith et al. 2006; Dhillo et al. 2007).…”
Section: Introductionmentioning
confidence: 99%